Impact of Entrepreneurial Education, Mindset, and Creativity on Entrepreneurial Intention: Mediating Role of Entrepreneurial Self-Efficacy - Jiatong, Wang; Murad, Majid; Bajun, Fu; Tufail, Muhammad Shahid; Mirza, Farhan; Rafiq, Muhammad (Frontiers in Psychology, 2021)
This study aimed to investigate the direct influence of entrepreneurial education, entrepreneurial mindset, and creativity on the entrepreneurial intention with the indirect role of entrepreneurial self-efficacy. This study applied structural equation model technique using AMOS software to verify the hypothesis relationships. This study collected self-administered survey data from 365 university students of Jiangsu and Zhejiang province of China. The findings indicated that entrepreneurial education, entrepreneurial mindset, and creativity have a positive and significant influence on entrepreneurial intention. Moreover, results revealed that entrepreneurial self-efficacy partially mediates in the relationship between entrepreneurial education, entrepreneurial mindset, and creativity on entrepreneurial intention. Further, implications and limitations were discussed in this article.